Stimbiotic supplementation and xylose-rich carbohydrates modulate broiler’s capacity to ferment fibre - Davies, Claire; González-Ortiz, Gemma; Rinttilä, Teemu; Apajalahti, Juha; Alyassin, Mohammad; Bedford, Michael R. (Frontiers in Microbiology, 2024)
Stimbiotics are a new category of feed additives that can increase fibre fermentability by stimulating fibre-degrading microbiota in the gut. The aim of this study was to test, ex vivo, if the microbiota of broilers fed a stimbiotic are better able to ferment different xylose-rich substrates in an ileal and a caecal environment. The ileal and caecal contents from broiler chickens fed a stimbiotic or from a control group were used as an inoculum in the ex vivo fermentation experiment. Different xylose-rich substrates including monomeric xylose (XYL), XOS with DP 2 to 6 (XOS), short DP XOS of 2 to 3 (sDP-XOS), long DP XOS of 4 to 6 (lDP-XOS) and de-starched wheat bran (WB), were added to This is a provisional file, not the final typeset article each ileal and caecal inoculum in fermentation vessels. Total gas, short-chain fatty acids (SCFA) production, bacterial quantification, and carbohydrate utilisation were monitored for 9 hours postinoculation. No significant interactions were observed in any of the parameters measured in either the ileal or caecal contents (P > 0.05). Stimbiotic ileal inocula resulted in higher total gas (P < 0.001) and volatile fatty acid (VFA) (P < 0.001) production, increased numbers of Lactobacillus spp. (P < 0.001), and decreased numbers of Enterococcus spp. (P < 0.01) after 9 hours regardless of the xylose-rich substrate added. Stimbiotic caecal inocula resulted in a higher ratio of VFA to branchedchain fatty acids (BCFAs) by up to +9% (P < 0.05). Ileal microbiota were found to preferentially metabolise WB, while caecal microbiota favoured XOS substrates, particularly lDP-XOS. These results indicate that stimbiotics can promote the abundance of lactic acid bacteria involved in the establishment of fibre-degrading bacteria and VFA content in the gut, which could have beneficial effects on broiler performance. Further, ileal and caecal microbiota differ in their utilisation of different substrates which may impact the effectiveness of different stimbiotic products.